The Prevalence of Bullying Among Pediatric Orthopaedic Patients. Issue 8 (22nd September 2021) - Carrillo, Laura A.; Sabatini, Coleen S.; Brar, Ravinder K.; Jagodzinski, Jason E.; Sabharwal, Sanjeev; Delgado, Eliana; Livingston, Kristin S.
Abstract : Background: Bullying is destructive and pervasive. Although the literature suggests children with chronic health conditions are at higher risk of being bullied, there is minimal research regarding the prevalence of bullying among children with orthopaedic conditions. Our study aimed to assess the prevalence of bullying among pediatric orthopaedic outpatients and evaluate the association of orthopaedic conditions and use of orthopaedic devices with perceptions of bullying. Methods: Patients in outpatient pediatric orthopaedic clinics, ages 10 to 17 and their parents were surveyed using the Child-Adolescent Bullying Scale-9. Basic demographic, information about the child's orthopaedic condition, and parent's perception of their child being subject to bullying were also collected. Children were asked if they had used any orthopaedic devices in the last 3 months, whether they were bullied because of their device, and if bullying affected their compliance with device use. The analysis utilized a t test or analysis of variance to compare mean Child-Adolescent Bullying Scale-9 scores across different groups. Results: Among the 198 patients surveyed, 61% (N=121) perceived no-to-minimal exposure to bullying, 36% (N=72) moderate exposure, and 3% (N=5) severe exposure. Children ages 10 to 13 (N=100) and children ages 14 to 17 (N=98) reported similar rates of bullying ( P =0.97). Higher rates of moderate to severe bullying were reported by patients with foot deformity (80%), multiple orthopaedic diagnoses (55%), chronic pain (39%), fracture/acute injury (37%), and scoliosis (33%). Moderate to severe bullying was reported by 37% of patients who wore a cast, 40% who wore a brace/orthotic, and 52% who used multiple orthopaedic devices. Parental concern that their child was being bullied was highly correlated with their child's bullying score ( P =0.0002). Conclusions: More than one third of our pediatric orthopaedic outpatients (39%) experience moderate to severe levels of bullying, which is higher than the general population's reported rates of 20% to 35%. Exposure to bullying may be higher in certain diagnoses or with use of certain orthopaedic devices. Further research is needed to delineate who is at highest risk. Level of Evidence: Level IV.